2008
DOI: 10.1016/j.envres.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Common household activities are associated with elevated particulate matter concentrations in bedrooms of inner-city Baltimore pre-school children

Abstract: Asthma disproportionately affects inner-city, minority children in the U.S. Outdoor pollutant concentrations, including particulate matter (PM), are higher in inner-cities and contribute to childhood asthma morbidity. Although children spend the majority of time indoors, indoor PM exposures have been less extensively characterized. There is a public health imperative to characterize indoor sources of PM within this vulnerable population to enable effective intervention strategies. In the present study, we soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
4
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 20 publications
4
87
4
10
Order By: Relevance
“…Current recommendations for improving home indoor air quality focus mostly on avoiding indoor SHS. However, our findings are likely independent of SHS exposure, and there are other important modifiable sources of indoor PM and NO 2 (20,40). Future studies investigating the effectiveness of environmental interventions aimed at reducing indoor pollutant concentrations in homes of patients with COPD, such air cleaner intervention trials that have shown reduction in indoor PM and improved symptoms in asthma (10), are warranted as potential nonpharmacologic approaches to improving COPD health.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Current recommendations for improving home indoor air quality focus mostly on avoiding indoor SHS. However, our findings are likely independent of SHS exposure, and there are other important modifiable sources of indoor PM and NO 2 (20,40). Future studies investigating the effectiveness of environmental interventions aimed at reducing indoor pollutant concentrations in homes of patients with COPD, such air cleaner intervention trials that have shown reduction in indoor PM and improved symptoms in asthma (10), are warranted as potential nonpharmacologic approaches to improving COPD health.…”
Section: Discussionmentioning
confidence: 78%
“…Our results are derived from a population in Baltimore City and surrounding areas and the indoor environment may not be generalizable to other communities. In addition, we did not measure outdoor or personal exposure to PM and NO 2 ; however, previous results from Baltimore City homes show that although outdoor PM and NO 2 concentrations contribute to indoor concentrations, indoor sources, such as smoking, cooking, combustion sources, and cleaning practices, are the dominant determinants of indoor pollutant concentrations (20,40). To confirm a similar association in our sample of homes of subjects with COPD, in a subgroup (n ¼ 26) of our participants who lived within 3 miles of an outdoor monitoring station, we found that outdoor PM 2.5 concentrations explained only 5% of the variance in indoor PM 2.5 concentrations; outdoor NO 2 concentrations explained approximately 25% of the variance in indoor NO 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Human-made sources consist of industrial emissions and combustion by-products from incinerators, motor vehicles, and power plants. Indoor sources include cigarette smoking, cooking, wood and other biomass burning in stoves and fireplaces, cleaning activities that re-suspend dust particles (e.g., sweeping), and penetration of outdoor particles into the indoor environment (11,12). Indoor PM differs from outdoor PM in source, composition, and concentration (11,(13)(14)(15)(16).…”
Section: Indoor Particulate Mattermentioning
confidence: 99%
“…A longitudinal study of 150 inner city preschool children with asthma, conducted as a part of the Johns Hopkins Center Significant determinants of indoor PM concentrations included smoking, sweeping, and stove use (19), activities that are modifiable and provide opportunities for exposure reduction. Smoking has been consistently described as a major source of indoor particulates over the last several decades, with more than 30% of all U.S. children exposed to secondhand smoke (20).…”
Section: Indoor Particulate Mattermentioning
confidence: 99%
“…Cigarette smoke is a major contributor to indoor PM in US homes, because each half-pack of cigarettes smoked in the home is estimated to contribute 4.0 μg/m 3 of PM, 7, 60 and approximately 30% of all US children and 40% to 60% of US children in low-income households are exposed to SHS in their homes. 7,65,66 Smoking cessation by close family members and caregivers is the most effective way to reduce or eliminate tobacco smoke exposure.…”
Section: Shsmentioning
confidence: 99%